The Sajogyo Development Paradigm and its Relevance for the Development of Coastal Areas in Indonesia - Rilus A Kinseng (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2024)
Prof. Sajogyo is one of the founders of rural sociology in Indonesia. He concerned himself very intensely with the problems of rural communities, especially rural poverty. In observing the current phenomenon of coastal communities, which are still highly characterized by poverty and social conflict, retracing Prof. Sajogyo’s conception on rural development becomes very important and pertinent. This article was written using a literature review method by exploring the thoughts of Prof. Sajogyo from his writings and from several other relevant writers. The aim of this study is to trace the Sajogyo development paradigm which is relevant to the development of coastal areas in Indonesia. This study shows that “The Sajogyo development paradigm” can be summarized to “equal and civilized welfare”. This means, in terms of content, for Prof. Sajogyo, development means increasing welfare or prosperity (growth dimension), especially for the lower class, the weak, and of course, the poor (equality dimension). Meanwhile, from the aspect of process, various efforts to improve welfare must be carried out in a civilized manner, namely by upholding dialogue, participation, capability, sovereignty, independence, and dignity of the poor and the weak. Thus, the Sajogyo development paradigm is conflict-sensitive and guarantees human security.